2021
DOI: 10.47836/pjssh.29.2.16
|View full text |Cite
|
Sign up to set email alerts
|

Webinar-Based Capacity Building for Teachers: “Lifeblood in Facing the New Normal of Education”

Abstract: Webinars as an avenue for professional development training remain to be scarcely explored, impeding the innovations in human resource development, which, if left unresolved, could have detrimental consequences to the professionals and ultimately, the economy. This study responded to this gap by exploring and examining the meanings around webinars as capacity-building for professionals from the point of view of the teachers. Guided by the post-modern, constructivist philosophical stance, interpretive hermeneut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…This agrees in the study of Tanucan & Uytico (2021), webinars serves as a crucial forum for official professional discussions. In the same regard, Abel et.al., (2021) found that webinars provides a way to ensure lifelong learning.for professional educators and assists them in adapting to the new educational standard.…”
Section: "I Was Able To Develop My Skills In Terms Of Being Flexible ...supporting
confidence: 81%
“…This agrees in the study of Tanucan & Uytico (2021), webinars serves as a crucial forum for official professional discussions. In the same regard, Abel et.al., (2021) found that webinars provides a way to ensure lifelong learning.for professional educators and assists them in adapting to the new educational standard.…”
Section: "I Was Able To Develop My Skills In Terms Of Being Flexible ...supporting
confidence: 81%
“…They provided training opportunities for teachers in "content, pedagogy, leadership, management, online teaching and learning and mental health" (Ancho & Arrieta, 2021, p. 25). They enhanced teachers' pedagogical, technological and research knowledge (Sakulprasertsri et al, 2022), life-long learning skills (Alvarez & Corcuera, 2021), knowledge of synchronous and asynchronous online teaching (Tanucan & Uytico, 2021), and collaborative knowledge construction (Toquero & Talidong, 2020). In addition, teachers valued the ease of accessibility and geographical flexibility of webinars (Gegenfurtner et al, 2020).…”
Section: Professional Development Webinarsmentioning
confidence: 99%
“…Skills are learned and improved by attending webinars. Teachers can improve their acquired skills through webinars and can develop new skills for their learners (Karalis, 2020;Tanucan & Uytico, 2021). Moreover, the teachers' skills are honed through webinars.…”
Section: Teachers' Expectations Of Attending Webinarsmentioning
confidence: 99%